2023
DOI: 10.2196/48000
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Factors That Affect the Uptake of Digital Therapeutics Within Health Systems: Scoping Review

Robin van Kessel,
Andres Roman-Urrestarazu,
Michael Anderson
et al.

Abstract: Background Digital therapeutics are patient-facing digital health interventions that can significantly alter the health care landscape. Despite digital therapeutics being used to successfully treat a range of conditions, their uptake in health systems remains limited. Understanding the full spectrum of uptake factors is essential to identify ways in which policy makers and providers can facilitate the adoption of effective digital therapeutics within a health system, as well as the steps developers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 260 publications
(1,210 reference statements)
0
17
0
Order By: Relevance
“…Co-design should continue throughout the lifecycle of the product to ensure that the product is adapted to meet users’ changing needs and sustained within health systems in flux. A recent review by van Kessel et al mapped the factors affecting the widespread uptake of digital health innovations in health systems [ 44 ]. Their review suggests that some of the frequently reported factors affecting uptake include developing sustainable funding options, robust digital infrastructure, novel professional guidelines and protocols, ongoing digital health training, interoperability across the health system, and tailoring to account for different needs across populations and disease stages [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-design should continue throughout the lifecycle of the product to ensure that the product is adapted to meet users’ changing needs and sustained within health systems in flux. A recent review by van Kessel et al mapped the factors affecting the widespread uptake of digital health innovations in health systems [ 44 ]. Their review suggests that some of the frequently reported factors affecting uptake include developing sustainable funding options, robust digital infrastructure, novel professional guidelines and protocols, ongoing digital health training, interoperability across the health system, and tailoring to account for different needs across populations and disease stages [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by van Kessel et al mapped the factors affecting the widespread uptake of digital health innovations in health systems [ 44 ]. Their review suggests that some of the frequently reported factors affecting uptake include developing sustainable funding options, robust digital infrastructure, novel professional guidelines and protocols, ongoing digital health training, interoperability across the health system, and tailoring to account for different needs across populations and disease stages [ 44 ]. The results of our paper corroborate the findings of van Kessel et al, and suggest that the value of co-design would be diminished if patient-public insights are not used to foster the viability of digital health innovation.…”
Section: Discussionmentioning
confidence: 99%
“…As supported by the literature [ 30 , 31 , 34 ], an introductory video and language that is understandable across all health literacy levels can enhance familiarity with technology and user engagement in a prospective mHealth app. mHealth apps provide a direct communication pathway to the exchange of information [ 34 ] and the interoperability of mHealth apps in clinical workflows may improve care delivery [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the sociotechnical aspects of these challenges in existing technologies and PN workflows [ 27 , 28 ] from the perspectives of BC patients, PNs, and oncology care providers (OCPs) is needed. The human-centered design (HCD) framework [ 29 ], which emphasizes understanding people and their needs, engaging stakeholders early on and throughout the design process and designing a solution for their needs, can provide insights into these complex care challenges from patient and provider perspectives and offer design solutions to respond to these needs [ [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation